Supercapacitor in battery charges of photovoltaic panel: analysis of the technical feasibility - Barbosa, Victor (2019)
The power generation from photovoltaic sources is variable and may contain unhoped fluctuations, which can be relieved by using energy storage systems. However, there is a technical contradiction in extracting the maximum power from a photovoltaic panel and the charge cycle of a battery. To overcome this problem, this paper presents an improvement consisting in a collaborative association of lithium ion batteries and supercapacitors showing the technical feasibility in a photovoltaic system. The structure of the energy conversion system was developed and was set up the converter’s configuration, design and operation simulation. The power management of full system implementation was simulated and the results are presented. The proposed system development and it technical analysis was carried out for both situations, with and without the use of supercapacitor. It was concluded that the supercapacitor in the photovoltaic systems bring better charging conditions, resulting in shorter charging times and better system performances.